Systems of Writing Response: A Brazilian Student's Experiences Writing for Publication in an Environmental Sciences Doctoral Program. - Simpson, Steve (Research in the Teaching of English, 2013)
The article focuses on the adoption of system based approach by the non-English graduate student for preparing scientific articles for publication. It demonstrates a study on how students develop their writing, translating, and preparation of scientific article for journal submission and revision of their doctoral dissertation on environmental science. It mentions the responses to their research writing from advisors, graduate peers, and journal reviewers.